Effect of dexamethasone on carrageenin-induced inflammation in the lung - S. F. Smith; A. Benjamin; A. Dewar; M. Sheppard; B. Fox; T. Smith; A. Guz; T. D. Tetley (Mediators of Inflammation)
To study the anti-inflammatory mechanisms of glucocorticoids, we have compared the effects of intratracheal carrageenin (2.5 mg) on control rats and those in which inflammation was subdued by prior dexamethasone treatment (10 mg/l in drinking water). Inflammation was maximal 48 h post-carrageenin. After dexamethasone, carrageenin caused tittle inflammation or oedema (wet lung (mg), n = 6, mean ± S.E.M.; control, 995 ± 51; carrageenin + dexamethasone, 1144 ± 83; compared with carrageenin alone, 1881 ± 198), but rats had more lung lavage neutrophils than those given carrageenin alone (PMN × 106 /lung, mean ± S.E.M.; control, 0.055 ± 0.003; carrageenin + dexamethasone, 8.54 ± 1.52; compared with carrageenin alone, 6.30 ± 1.71). Proteolysis and partial inactivation of the anti-inflammatory mediator, lipocortin 1 (Lcl), in carrageenin-instilled rats was offset in those also given dexamethasone, by increased Lc1 levels (intact Lc1 ng/ml lavage fluid, n = 4, mean ± S.E.M.; control 24 ± 6; carrageenin 15 ± 4; carrageenin + dexamethasone, 40 ± 15). Maintenance of sufficient intact (fully active) extracellular Lc1 may contribute to the actions of glucocorticoids.